Implementation of Mind Mapping Learning Methods in Efforts to Improve the Research and Examination of Seminars on the College of Public Policy Seminar as FISIP UMSU Products - Dedi Amrizal; Yusriati Yusriati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Teaching Grant using mind mapping method is expected to be a reference in improving the learning system in public policy seminar courses in the Faculty of Political Science (FISIP), especially the State Administration Study Program (IAN). The low condition of mastery of the problem and the lack of ability to explain problems at the time of the seminar practice in this public policy seminar course made researchers interested in offering new learning methods with the name mind mapping that prioritizes images and signs for mapping research problems as well as can be used to help The student explained the research problem more clearly during the thesis proposal seminar. This study aims to assist students in finding research problems properly, improving students' ability in formulating problems and explaining problems in public policy seminars and ultimately expected to improve the quality of seminars and the quality of student answers in public policy seminars. The results showed that in the first cycle there was no significant development of the students involved so it was necessary to do a second cycle with the addition and improvement when training and making mind mapping and presentation. Finally in the second cycle, it can be seen that there are changes and improvements in the making of mind mapping and it can be seen that students find it easier to explain the research problem compared to mind mapping learning methods that can increase students' mastery of research problems and can facilitate them in explaining the problems at the seminar. Although the final achievement of the first cycle still shows confusion and low mastery of the mind mapping theory, in the second cycle there is a change in the mastery of theory and mind mapping (students realize that mind mapping cannot be done if they do not master the research problem correctly) so when explaining the problem of research in front of the class when the seminar practice takes place can be done better. In general, the use of mind mapping in public policy seminar courses is very useful and helps students in formulating research problems, making a research background, presenting a research background in the form of a power point containing mind mapping. And the most important thing is that mind mapping helps students in explaining the research problem at the time the seminar was held.